A Conceptual Framework for Collaborative Development of Intelligent Construction and Building Industrialization - Guo, Zhenxu; Li, Lihong (Frontiers in Environmental Science, 2022)
Digitization can substantially impact intelligent construction and building industrialization (ICBI). Realizing the collaborative development of ICBI has become one approach for the transformation and upgrading of the construction industry, which also has attracted growing attention. Due to the lack of application scenarios and the imperfect management platform, it is difficult for construction enterprises to participate in the practical engineering project in this work. Furthermore, the literature lacks consensus on the collaborative development of ICBI to affect the construction industry. To respond to this problem, a conceptual framework applicable for ICBI, which reflects the current status of China's construction industry, is required for construction enterprises. Consequently, this paper proposes a "mi"-shaped conceptual framework with synergy theory, wherein stakeholders' collaboration, industrial collaboration, structural collaboration, building technology upgrading, factor endowment upgrading, innovation service upgrading, and construction process upgrading were analyzed. In parallel, the conceptual framework indicates the direction for the collaborative development of ICBI from four dimensions: dual drive, resource supply, collaborative operation, and trust guarantee. The research results will help form an intelligent system and realize the industrialization for new buildings to drive sustainable development in the construction industry.